Lord Jim [videorecording (DVD)] - Brooks, Richard, 1912-1992; O'Toole, Peter, 1932-2013; Mason, James, 1909-1984; Jürgens, Curd, 1915-1982; Wallach, Eli, 1915-2014; Conrad, Joseph, 1857-1924 (Sony Pictures choice collection, 2012)
The story of an idealistic Merchant Marine officer who disgraces himself when he abandons his ship.